Home-Advantage during COVID-19: An Analysis in Portuguese Football League - Matos, Rui (2021)
Covid-19 pandemic forced, at the final rounds of 2019–2020 season, in many different sports leagues worldwide, teams to play without an audience. Therefore, the present paper aims to compare the home advantage score in the last ten rounds in the 2019–2020 season with the first 24 rounds in the same season using Pollard’s (1986) and Matos et al.’s (2020) methods. In addition, comparisons across different seasons (2016–2017; 2017–2018; 2018–2019 and 2019–2020) using the same methods were also analyzed. Results showed no differences (p > 0.05) between first 24 rounds and the last 10 in 2019–2020 season as well as in the 3 previous seasons. With Pollard’s method, no differences (p > 0.05) were also found among those four seasons on global (all 34 rounds) home advantage. However, a significance difference between 2017–2018 and 2019–2020 (p < 0.05) was founded using Matos et al.’s (2020) method, which is an indicator of the importance of using complementary methods when analyzing the same realities. Overall, despite what might be expectable from recent findings, the lack of an audience in the last 10 rounds of Portuguese Football League 2019–2020 season, due to COVID-19 pandemic, did not affect home advantage. Therefore, future studies could try to analyze other different variables in Portuguese Football League, such as referees’ behaviors, rules changing (e.g., the possibility of making five substitutions, instead of three), crowd dimension and density as well as include variables about odds as forecasts in football being played without crowds.